2022
DOI: 10.21203/rs.3.rs-1770054/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Non-Small-Cell Lung Cancer Promotion by Air Pollutants

Abstract: Environmental carcinogenic exposures are major contributors to global disease burden yet how they promote cancer is unclear. Over 70 years ago, the concept of tumour promoting agents driving latent clones to expand was first proposed. In support of this model, recent evidence suggests that human tissue contains a patchwork of mutant clones, some of which harbour oncogenic mutations, and many environmental carcinogens lack a clear mutational signature. We hypothesised that the environmental carcinogen, <2.5μ… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 29 publications
1
5
0
Order By: Relevance
“…In the absence of smoking-associated field cancerization or known familial predisposition, the presence of multiple synchronous EGFR -mutant tumors appears paradoxical, and several distinct models have been proposed. Deep sequencing of normal lung tissues has revealed rare oncogenic EGFR mutant alleles in 18% of samples 29 , consistent with the emerging appreciation that cancer-causing mutations may populate apparently healthy aging tissues 3034 . Any tumors ultimately derived from such mutant EGFR -harboring cells would constitute independent genetic events.…”
Section: Introductionsupporting
confidence: 61%
See 2 more Smart Citations
“…In the absence of smoking-associated field cancerization or known familial predisposition, the presence of multiple synchronous EGFR -mutant tumors appears paradoxical, and several distinct models have been proposed. Deep sequencing of normal lung tissues has revealed rare oncogenic EGFR mutant alleles in 18% of samples 29 , consistent with the emerging appreciation that cancer-causing mutations may populate apparently healthy aging tissues 3034 . Any tumors ultimately derived from such mutant EGFR -harboring cells would constitute independent genetic events.…”
Section: Introductionsupporting
confidence: 61%
“…Recent studies in barrier organs, including skin and esophagus, have indicated that as they age, histologically normal tissues may acquire canonically oncogenic mutations that give rise to small patches of clonal expansion, but without evidence of frank malignancy 3034 . In the lung, deep sequencing reveals that up to 18% of normal samples have a detectable mutant EGFR allele, and even more cases harbor KRAS and other mutated oncogenes 29 . The high prevalence of normal lung specimens with rare detectable EGFR -mutant alleles due to field cancerization does not explain the occurrence of multiple EGFR -mutant primary tumors described here, since they would be genetically independent, lacking the multiple shared mutations that define the developmental mosaically-derived primaries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, very recent work by Swanton and colleagues has identified a potentially powerful mechanism through which PM 2.5 can contribute to non-small cell lung cancer (NSCLC) in non-smokers, a disease with a high frequency of EGFR mutations (EGFRm). The authors found that PM promotes precursor lung epithelial cells initiated by EGFRm [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that in the coming decades we may experience a new wave of lung cancers due to vaping, if indeed promotion is the rate limiting step for development of this disease. Recent data on links between air pollution and lung cancer in non-smokers support this possibility, as a combination of epidemiological, molecular, and mechanistic studies highlight the role of pollutants as promoters of lung cancers worldwide [52]. It would be regrettable if ignorance of these possible mechanisms results in dependence on future black box epidemiologists to identify a strong link between vaping and lung cancer.…”
Section: Integration Of Black Box and Mechanistic Approaches To Cance...mentioning
confidence: 99%